Kebijakan dan Regulasi Transportasi Berkelanjutan: Analisis Implementasi Energi Terbarukan dalam Sistem Transportasi Perkotaan - Dewi, Kemmala (LPPM Institut Pendidikan Nusantara Global, 2025)
The development of renewable energy-based transportation has become a strategic issue in addressing environmental challenges and energy efficiency in Indonesia’s urban transport sector. This study analyzes the implementation of renewable energy-based transportation systems in major Indonesian cities from the perspective of existing policies and regulations. The analysis covers technical, economic, social, and environmental aspects influenced by government policies and sustainable transportation regulations. The research methodology combines a review of national and regional policies, evaluation of operational data from five major cities (Jakarta, Surabaya, Bandung, Medan, and Semarang), and surveys of public transportation users. The results show that policies promoting electric vehicle adoption and supporting infrastructure development have significantly reduced carbon emissions by 85.9%, lowered operational costs by 37.8%, and increased user satisfaction by 42%. Jakarta stands out as the most advanced city in implementation, with 120 electric buses and 15 charging stations contributing to an 85% public transport occupancy rate and 94% service punctuality. Despite strong regulatory commitments, challenges remain in infrastructure standardization and interregional policy coordination, which hinder the broader development of sustainable transportation. Therefore, this study emphasizes the importance of strengthening systematic regulations, increasing infrastructure investment, and developing incentive schemes for the private sector to support the acceleration of the transition toward renewable energy-based transportation in Indonesia.